2014
DOI: 10.1002/stem.1779
|View full text |Cite
|
Sign up to set email alerts
|

Passage Number is a Major Contributor to Genomic Structural Variations in Mouse iPSCs

Abstract: Emergence of genomic instability is a practical issue in preparing neural stem cells (NSCs) and induced pluripotent stem cells (iPSCs). However, it is still not fully understood what the origins and mechanisms for formation are for the genomic alternations observed. Here, we studied the extent of genomic variation on the scale of individual cells originating from the same animal. We used mouse NSCs grown from embryonic cells and iPSCs generated from embryonic brain cells, B cells or fibroblasts, and performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…An initial characterization of the CNVs demonstrated substantial variability in the number of CNVs across the various lines and passages ( Fig. 2A and Supplementary Table S1), consistent with what has been previously reported in similar analyses [4][5][6]26]. Most iPSC CNVs were novel-only a minority was also present in parental fibroblast (Fig.…”
Section: Cnv Detection and Characterizationsupporting
confidence: 86%
“…An initial characterization of the CNVs demonstrated substantial variability in the number of CNVs across the various lines and passages ( Fig. 2A and Supplementary Table S1), consistent with what has been previously reported in similar analyses [4][5][6]26]. Most iPSC CNVs were novel-only a minority was also present in parental fibroblast (Fig.…”
Section: Cnv Detection and Characterizationsupporting
confidence: 86%
“…For example, isochromosome 12p is often undetectable in blood, but examination of cells of ectodermal origin frequently reveals the mosaic aneuploidy [93]. Culturing cell lines derived from individuals present similar challenges, not only because cells accumulate mutations as they undergo mitosis [94], but also because culture conditions exert selective forces. To overcome these limitations, other or multiple sources of primarily obtained DNA can be examined.…”
Section: Detection Of Mosaicismmentioning
confidence: 99%
“…To understand the scope of acquired genetic changes that occur during iPSC generation, previous studies have compared single nucleotide variants (SNVs), copy number variations (CNVs), and chromosomal rearrangements in iPSCs to donor somatic cells or embryonic stem cells (ESCs) using various assays, including SNP array and next-generation sequencing methods (1)(2)(3)(4)(5)(6). Whole genome or exome sequencing (WGS/ WES) of parental and iPSC pairs have demonstrated that there are, on average, 6-12 coding SNVs per iPSC line (1,(7)(8)(9) with varying theories regarding when these SNVs arose in the iPSCs.…”
mentioning
confidence: 99%